Linguistics and evolution : a developmental approach - Andresen, Julie Tetel, 1950- (Cambridge : Cambridge University Press, 2014)
'Evolutionary linguistics - an approach to language study that takes into account our origins and development as a species - has rapidly developed in recent years. Informed by the latest findings in evolutionary theory, this book sets language within the context of human biology and development, taking ideas from fields such as psychology, neurology, biology, anthropology, genetics and cognitive science. By factoring an evolutionary and developmental perspective into the theoretical framework, the author replaces old questions - such as'what is language?' - with new questions, such as'how do living beings become'languaging' living beings?' Linguistics and Evolution offers readers the first rethinking of an introductory approach to linguistics since Leonard Bloomfield's 1933 Language. It will be of significant interest to advanced students and researchers in all subfields of linguistics, and the related fields of biology, anthropology, cognitive science and psychology'--
Includes bibliographical references (pages 281-297) and indexes.
Keywords: Language and languages -- Origin; Human evolution; Information theory in biology; Anthropological linguistics